Analysis of Taxsee Driver User Satisfaction in Jambi City Using the Servqual Method - Josefi Virgi Narada; Beni Irawan; Chandy Ophelia; Amroni (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This research analyzes driver satisfaction levels in Jambi City using the Taxsee Driver application through the Service Quality (SERVQUAL) method. The study background is user complaints regarding GPS inaccuracies and the automatic order system that affects driver performance ratings. Data were collected via online questionnaires from 385 active drivers in Jambi City and processed using Structural Equation Model with SmartPLS. Results show that three of five SERVQUAL dimensions significantly affect user satisfaction: Tangibles (T-Statistic 5.073), Responsiveness (T-Statistic 3.782), and Empathy (T-Statistic 4.026). Reliability (T-Statistic 1.735) and Assurance (T-Statistic 1.303) were not significant. The R-Square value of 0.879 indicates the model explains 87.9% of user satisfaction variation. Developers are recommended to improve navigation accuracy and responsiveness to maintain driver partner loyalty.